APLIKASI PENJUALAN DAN PERSEDIAAN BARANG - Riyan Maulana; Novrini Hasti (PETIR, 2015)
Humblezing Store is one of the convection that produces a variety of clothing and men'sjackets. In producing goods company uses quality materials so that the products have high quality.Marketing system which runs today are using social media such as Facebook and BlackberryMessenger (BBM). This is done because most Indonesian people today prefer a company that offersthe ease of sale. The method used in the development of information systems sales and inventory isan engineering prototype. The system design modeling tool is a structured approach using toolssuch flowchart document (flowmap), context diagram, DFD (Data Flow Diagram), data dictionary,normalization, table relationships, and ERD (Entity Relationship diagrams). The programminglanguage used is PHP using MySQL database server. Results of this study were (1) With a system ofsales and inventory information is the consumers can find out information about Humblezing Storeonline. (2) The information system of sales and inventory that is proposed can improve and willprovide service to consumers. Consumers who want to make purchases do not have to comedirectly to the store, but can make purchases anywhere.